ESTIMASI NILAI PASAR WAJAR SAHAM MNC LAND PT (PERSERO) TBK DALAM RANGKA RIGHT ISSUE TAHUN 2014 - , Noor El Hasani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to estimate the fair market value of the shares of PT MNC Land Tbk by the end of 2013, when the company plans to fet fund through a rights issue scheme. Fair market value of the shares of PT MNC Land Tbk is obtained using several methods: discounted cash flowâto-equity cash flow, discounted cash flowâto-firm cash flow and relative valuation models with multiple PBV (Price to Book Value). The importance this study is to provide input and consideration for the company during a rights issue as well as additional useful information and resources for investors who might invest in PT MNC land Tbk. The data examined in this study on the method of discounted cash flow-to-equity cash flow and relative valuation models consist of six financial statements and other information contained in the annual report of PT MNC land Tbk year 2008-2013, the company's financial statements of comparable firms, price of shares PT MNC land Tbk, and the stock price index (CSPI). The results show that the fair market value of the shares of PT MNC land Tbk as on December 31, 2012 using the discounted cash flow-free cash flow to equity model is Rp1.291,- per share, the fair market value of the shares based on discounted cash flowâfree cash flow to firm model is Rp1.291,- and the fair market value of the shares based on relative valuation methods is Rp1.505,- per share. The results of the reconciliation of the two methods produce fair market value of the shares of PT MNC land Tbk amounting to Rp1.334,- per share. The range of fair market value as is Rp1.234 sale as the lower limit and with upper limit of Rp1.434,-